2019
DOI: 10.1371/journal.pone.0219046
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis reveals phenotypic diversity of Euscaphis japonica population

Abstract: Fruit traits affect population genetic diversity by affecting seed protection and dispersal strategies, thereby comprising important components of phenotypic variation. Understanding of the phenotypic variation is an indispensable first step for developing breeding strategies. However, little information is known about the genetic variation in E . japonica —a monotypic species with abundant phenotypes that is mainly distributed in southern China. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
13
2
Order By: Relevance
“…Similar results were revealed in evaluating the diversity of Pakistani guava germplasm (Mehmood et al 2014). The diversity of morphological characters in the studied guava collection in Vietnam also provides an ample scope for the selection of excellent individuals for further improvement as reported in previous studies (Purbajanti et al 2016, Sun et al 2019.…”
Section: (Very Many)supporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were revealed in evaluating the diversity of Pakistani guava germplasm (Mehmood et al 2014). The diversity of morphological characters in the studied guava collection in Vietnam also provides an ample scope for the selection of excellent individuals for further improvement as reported in previous studies (Purbajanti et al 2016, Sun et al 2019.…”
Section: (Very Many)supporting
confidence: 85%
“…Morphological characterization is the first and highly recommended step before further attempts utilizing biochemical or the currently most popular, molecular approaches in genetic diversity assessment and preservation studies (Sun et al 2019). In this study, the morphological characteristics of the most abundant guava × 100% MP (%) = SFW -Total seeds weight SFW Seed number SN 1 (none), 2 (very few), 3 (few), 5 (medium), 7 (many),…”
Section: Morphological Characteristics Of Guava Accessionsmentioning
confidence: 99%
“…According to Flora of China records, E. japonica is a deciduous tree or shrub with odd-pinnate leaves, papery leaflets, sparsely serrulate margins with glandular teeth, and a soft, red, leathery pericarp with irregular ribs ( Li, Cai & Wen, 2008 ). Previous studies have found that E. japonica exhibits significant phenotypic differences at different altitudes, and it can be classified as deciduous or evergreen based on its phenotypic markers ( Sun et al, 2019 ). The deciduous E. japonica was characterized by its papery leaflets, serrulate margins, and prominent epidermis ribs, and the evergreen E. japonica was characterized by its membranous leaflets with obtuse, serrate margins, and its inconspicuous fruit epidermis rib ( Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that E. japonica exhibits significant phenotypic differences at different altitudes, and it can be classified as deciduous or evergreen based on its phenotypic markers ( Sun et al, 2019 ). The deciduous E. japonica was characterized by its papery leaflets, serrulate margins, and prominent epidermis ribs, and the evergreen E. japonica was characterized by its membranous leaflets with obtuse, serrate margins, and its inconspicuous fruit epidermis rib ( Sun et al, 2019 ). However, evaluating genetic variations across different populations using morphological characters is difficult because plant morphology varies under different growing conditions ( Wang et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…These similarities can be due to changes in phenotypic traits. Populations in the same ecological conditions, in the long-term evolutionary process, form the same adaptation matrix to produce phenotypic similarities (Sun et al 2019). Close relationship between the accession of Bogor and Merapin Daun Kecil allegedly because these two varieties originated from the same parent.…”
Section: Agro-morphological Characters Of Black Pepper In Bangka Islandmentioning
confidence: 99%